2010
DOI: 10.1210/en.2009-1119
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Corticosterone Pulsatile Patterns Attenuate Responsiveness to Glucocorticoid Signaling in Rat Brain

Abstract: Chronically elevated circulating glucocorticoid levels are although to enhance vulnerability to psychopathology. Here we hypothesized that such sustained glucocorticoid levels, disturbing corticosterone pulsatility, attenuate glucocorticoid receptor signaling and target gene responsiveness to an acute challenge in the rat brain. Rats were implanted with vehicle or 40 or 100% corticosterone pellets known to flatten ultradian and circadian rhythmicity while maintaining daily average levels or mimic pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 49 publications
6
55
1
1
Order By: Relevance
“…We demonstrate that FKBP51 SUMOylation affects the expression of GILZ and SGK1, which are SUMOylation of FKBP51 regulates GR signaling M Antunica-Noguerol et al upregulated by GCs in the hippocampus. 33,34 In line with these results, our data show that GCs also induce the expression of SGK1 and GILZ in HT22 hippocampal neuronal cells. Moreover, we show that only SUMOylation-competent FKBP51 is involved in their regulation.…”
Section: Discussionsupporting
confidence: 87%
“…We demonstrate that FKBP51 SUMOylation affects the expression of GILZ and SGK1, which are SUMOylation of FKBP51 regulates GR signaling M Antunica-Noguerol et al upregulated by GCs in the hippocampus. 33,34 In line with these results, our data show that GCs also induce the expression of SGK1 and GILZ in HT22 hippocampal neuronal cells. Moreover, we show that only SUMOylation-competent FKBP51 is involved in their regulation.…”
Section: Discussionsupporting
confidence: 87%
“…Repetitive corticosterone exposure results in transient cyclic recruitment and exchange of GR at regulatory sites in the genome (Stavreva et al, 2009;Conway-Campbell et al, 2010), whereas MR is retained in the nucleus (Conway-Campbell et al, 2007). Experimental evidence supports the idea that pulsatile patterns are necessary to safeguard GR sensitivity and downstream signaling in target tissues (Sarabdjitsingh et al, 2010b).…”
Section: E Transcriptional Regulationmentioning
confidence: 83%
“…Similarly, it would be of interest to follow metaplastic changes for more than the current 2-h range. Finally, several studies have shown that nuclear GR signaling-e.g., translocation, binding, and transcription of target genes-normalizes to baseline levels between pulses (4,(6)(7)(8). It is therefore of great interest to resolve in detail if and particularly how a first pulse of CORT could lead to enhanced surface expression of GRs and which signaling pathways underlie the reversal exerted by the second pulse on processes activated by the first pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse amplitudes steeply rise some hours before awakening and then slowly diminish again (5). The functional relevance of ultradian pulses is only starting to be understood; recent evidence suggests that pulses are necessary to maintain optimal transcriptional activity of GRs (4)(5)(6)(7)(8), thus coordinating essential bodily functions in preparation of the active phase.…”
mentioning
confidence: 99%